Impotence and genital numbness in cyclists - Sommer, F.; König, D.; Graf, C.; Schwarzer, U.; Bertram, C.; Klotz, T.; Engelmann, U. (International Journal of Sports Medicine, 2001)
Cyclists often complain of genital numbness and even of impotence. The purpose of this study was to determine if perineal compression during cycling causes changes in the penile blood supply, impotence and penile numbness. Forty healthy athletic men with a mean age of 30 +/- 5.3 years took part in the study. Transcutaneous penile oxygen pressure was obtained using a device consisting of a modified Clark pO2 electrode, attached to the glans of the penis. All men were measured in a standing position before, in a seated and standing position during and in a standing position after cycling. Additionally, a detailed interview was carried out with each man. The penile blood supply--which correlates with the transcutaneous PO2 at the glans-- decreased significantly in over 70% of the test subjects during cycling in a seated position. Cycling in a standing position did not show any alteration in the penile blood supply as compared to the values measured before exercising. Numbness of the genital region was reported by 61% of the cyclists. 19% of cyclists who had a weekly training distance of more than 400 km complained of erectile dysfunction. The results of the present study showed that there is a deficiency in penile perfusion due to perineal arterial compression. This could be a reason for penile numbness and impotence in long-distance cyclists. Therefore, we suggest restricting the training distance, and taking sufficient pauses during the course of prolonged and vigorous bicycle riding, in order to avoid penile numbness and impotence.